The IMF and precautionary lending: An empirical evaluation of the selectivity and effectiveness of the flexible credit line - Dennis Essers; Stefaan Ide (National Bank of Belgium, 2017)
This paper provides an empirical evaluation of the Flexible Credit Line (FCL), the IMF's prime precautionary lending instrument since 2009 to which so far only three emerging market economies have subscribed: Mexico, Colombia and Poland. We consider both questions of selectivity and effectiveness: first, which factors explain the three FCL countries' participation in such arrangements? And second, to which extent have the FCL arrangements delivered on their promise of boosting market confidence in their respective users? Based on a probit analysis we show that FCL selectivity can be explained by both demand- and supply-side factors. The probability of participation in the FCL was greater in countries that experienced larger exchange market pressures prior to the creation of the instrument, that had lower bond spreads and inflation, that accounted for higher shares in US exports, and that exhibited a higher propensity of making political concessions to the US. Our estimation of the effects of the FCL employs the 'synthetic control' methodology, a novel counterfactual approach. We find evidence for some but not spectacular beneficial effects on sovereign bond spreads and gross capital inflows in FCL countries. Overall, our results suggest that any economic stigma eligible countries still attach to entry into an FCL arrangement is unwarranted. Conversely, the apparent link of FCL participation with US interests may not be conducive to overcoming political stigma.
Keywords: F33; F34; F55; 330; Flexible Credit Line; IMF; global financial safety net; emerging markets; synthetic control